2018
DOI: 10.1002/jcp.26787
|View full text |Cite
|
Sign up to set email alerts
|

TANK‐binding kinase 1 and Janus kinase 2 play important roles in the regulation of mitogen‐activated protein kinase phosphatase‐1 expression after toll‐like receptor 4 activation

Abstract: Inflammation is a response that protects the body from pathogens. Through several inflammatory signaling pathways mediated by various families of transcription factors, such as nuclear factor-κB (NF-κB), activator protein-1 (AP-1), interferon regulatory factors (IRFs), and signal transducers and activators of transcription (STATs), various inflammatory cytokines and chemokines are induced and inflammatory responses are boosted. Simultaneously, inhibitory systems are activated and provide negative feedback. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…The sgRNA was cloned within a lentiCRISPRv2 vector (plasmid ID #52961; Addgene, Cambridge, MA, USA). Transfection and puromycin (1–3 μg/mL) selection were completed using a previously established protocol [ 38 ]. To prepare control wild type (WT) cell line, we transfected TrueGuide™ sgRNA negative control, non-targeting 1 (Invitrogen, Cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sgRNA was cloned within a lentiCRISPRv2 vector (plasmid ID #52961; Addgene, Cambridge, MA, USA). Transfection and puromycin (1–3 μg/mL) selection were completed using a previously established protocol [ 38 ]. To prepare control wild type (WT) cell line, we transfected TrueGuide™ sgRNA negative control, non-targeting 1 (Invitrogen, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages display different gene expression and protein activity according to duration of LPS exposure, and STAT3 plays an active role in the inflammatory process [ 36 , 37 , 38 ]. We wished to investigate the intracellular inflammatory signaling of STAT3 at several time points during LPS exposure in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…This series of signal transductions promotes the activation of various immune response genes namely, nuclear factor kappa B (NF-κB), transcription factor complex activator protein-1 (AP-1), and interferon regulatory factors (IRFs) and induces the expression of various cytokines and adhesion molecules associated with the inflammatory response. This has become recognized as a pathogenic mechanism of AS (Kim et al, 2018). Oxidative stress and cellular damage activate TLR4, leading to the expression of inflammatory mediators (Zhu et al, 2021).…”
Section: Tlr4 Signaling Pathwaymentioning
confidence: 99%
“…Tbk1 is a IκB-related kinase that activates NF-κB after forming a complex with the IκB proteins Tank and Traf2 [54]. Studies also revealed that a high level of Tbk1 triggered an MAPK phosphatase-1-mediated negative feedback pathway to control inflammation [55]. The epigenetic regulation of tkb1 may be involved in controlling the inflammatory response triggered by plant protein-based diets and in maintaining the intestinal homoeostasis in zebrafish.…”
Section: Discussionmentioning
confidence: 99%